Pengaruh Promosi Internal terhadap Keputusan Pembelian Tamu pada Garden Restaurant Grand Savoy Homann Bidakara Hotel Bandung - Prima Setia Judha Pranatha (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2020)
Internal promotion is one of the marketing strategies by utilizing messages and media as a means of delivery to achieve the goals of the sales company. This study aims to see any major influence of promotion on guest purchasing decisions at the Garden Restaurant, Grand Savoy Homann Bidakara Hotel Bandung. The research method used is descriptive statistics. The data technique was carried out through literature studies, interviews and questionnaires, where the data were obtained through questionnaires to guests which were distributed to 100 respondents. The sample population in this study were consumers of the Garden Restaurant Grand Savoy Homann Bidakara Hotel Bandung using an accidental sampling technique. The data analysis technique used is multiple linear regression with the help of SPSS. The results showed that overall the Message (X1) and Media (X2) variables, the purchase decision (Y) had quite a positive effect, namely 64.98%. Where the Message variable (X1) has a greater influence, namely 46.34% while the Media variable (X2) is 18.55% based on the results based on path analysis